1996
DOI: 10.1046/j.1365-2249.1996.d01-804.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of salmeterol on the respiratory burst of adherent human neutrophils

Abstract: SUMMARYHuman neutrophils, plated in fibronectin-coated wells and stimulated with N-formyl-methionyl-leucylphenylalanine (fMLP), were found to undergo a massive and prolonged respiratory burst, as measured by monitoring superoxide production. The 2 -agonist salmeterol inhibited the respiratory burst in a dose-dependent manner. In contrast, salbutamol was ineffective. Moreover, the neutrophil respiratory burst was partially suppressed by prostaglandin E 2 (PGE 2 ) and the phosphodiesterase type IV (PDE-IV) inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Although corticosteroids are felt to be less effective in modulating neutrophil function compared with other effector cells, such as eosinophils or mast cells [28], several reports suggest that ICScontaining regimens may reduce sputum neutrophilia in patients with COPD [29,30], perhaps by decreasing neutrophil chemotaxis [31]. However, there is some evidence that SAL may alter neutrophil function either through decreased adhesion to airway epithelium [32] or capillary endothelium [33] or by inhibiting respiratory burst activity [34]; yet an increase in the pneumonia signal was not observed with SAL therapy in this trial. The observation of a pneumonia signal was unexpected and TORCH was not designed to address the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Although corticosteroids are felt to be less effective in modulating neutrophil function compared with other effector cells, such as eosinophils or mast cells [28], several reports suggest that ICScontaining regimens may reduce sputum neutrophilia in patients with COPD [29,30], perhaps by decreasing neutrophil chemotaxis [31]. However, there is some evidence that SAL may alter neutrophil function either through decreased adhesion to airway epithelium [32] or capillary endothelium [33] or by inhibiting respiratory burst activity [34]; yet an increase in the pneumonia signal was not observed with SAL therapy in this trial. The observation of a pneumonia signal was unexpected and TORCH was not designed to address the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Salmeterol reduces neutrophilic inflammation induced by inhaled endotoxin in mice [34]. LABAs inhibit neutrophil respiratory burst [35] and reduce adhesion of neutrophils to airway epithelial cells through inhibition of the expression of CD11b/CD18 on the neutrophil surface [36]. LABAs also reduce airway microvascular leakage, which is increased in COPD [37][38][39], all of which suggest an anti-inflammatory profile.…”
Section: Long-acting Bronchodilatorsmentioning
confidence: 99%
“…We have shown that sex differences in the inflammatory response in rats are adrenal medulla dependent (Green et al, 1999), and that activation of the sympathoadrenal system by stress or noxious stimulation inhibits the inflammatory response (Green et al, 1997;Strausbaugh et al, 1999). It is likely that adrenaline plays an important role, since it is a principal adrenal medulla mediator and the inflammatory response can be regulated through b 2 -adrenergic receptor activation (Coderre et al, 1990;Ottonello et al, 1996;Barnes, 1999;Mills et al, 2000). While the cellular site of action of adrenaline on the inflammatory response is currently unknown, b 2 -adrenergic receptors in humans are constitutively expressed in a wide variety of tissues including immune cells, where activation of these receptors leads to anti-inflammatory actions, for example, by regulation of cytokine production in leucocytes, reduction of plasma exudation and cell adhesion to activated endothelial cells (Barnes, 1999;Johnson, 2002).…”
Section: Introductionmentioning
confidence: 98%